The differential effect of metabolic alkalosis on maximum force and rate of force development during repeated, high-intensity cycling - Siegler, J. C.; Marshall, P. W. M.; Raftry, S.; Brooks, C.; Dowswell, B.; Romero, R.; Green, S. (Journal of Applied Physiology, 2013)
The purpose of this investigation was to assess the influence of sodium bicarbonate supplementation on maximal force production, rate of force development (RFD), and muscle recruitment during repeated bouts of high-intensity cycling. Ten male and female (n = 10) subjects completed two fixed-cadence, high-intensity cycling trials. Each trial consisted of a series of 30-s efforts at 120% peak power output (maximum graded test) that were interspersed with 30-s recovery periods until task failure. Prior to each trial, subjects consumed 0.3 g/kg sodium bicarbonate (ALK) or placebo (PLA). Maximal voluntary contractions were performed immediately after each 30-s effort. Maximal force (Fmax) was calculated as the greatest force recorded over a 25-ms period throughout the entire contraction duration while maximal RFD (RFDmax) was calculated as the greatest 10-ms average slope throughout that same contraction. Fmax declined similarly in both the ALK and PLA conditions, with baseline values (ALK: 1,226 ± 393 N; PLA: 1,222 ± 369 N) declining nearly 295 ± 54 N [95% confidence interval (CI) = 84-508 N; P < 0.006]. RFDmax also declined in both trials; however, a differential effect persisted between the ALK and PLA conditions. A main effect of condition was observed across the performance time period, with RFDmax on average higher during ALK (ALK: 8,729 ± 1,169 N/s; PLA: 7,691 ± 1,526 N/s; mean difference between conditions 1,038 ± 451 N/s, 95% CI = 17-2,059 N/s; P < 0.048). These results demonstrate a differential effect of alkalosis on maximum force vs. maximum rate of force development during a whole body fatiguing task.